A sustainable manufacturing method of thermoset composites based on covalent adaptable network polymers. (15th September 2021) - He, Xu; Shi, Xiaojuan; Chung, Christopher; Lei, Zepeng; Zhang, Wei; Yu, Kai
Abstract: Sustainable manufacturing of polymer composites has received increasing global attention. Existing industrial manufacturing methods rapidly consume natural resources and generate significant manufacturing wastes that are difficult to recycle. In this study, we develop a sustainable manufacturing method for thermoset composites based on the dynamic features of covalent adaptable network (CAN) polymers. It uses the scrap polymer wastes as feedstock to fabricate solid polymer films with tailored thicknesses. They are used to manufacture composite lamina with controlled fiber contents via hot pressing, wherein the malleable matrix fuses into the fiber fabric and welds them together. Both fiber and thermoset matrix can be recycled for the next round of manufacturing. The composites exhibit near-identical mechanical performance in each manufacturing cycle as the ones directly molded with the polymer solution. The fabricated composites are malleable and can be readily reprocessed into different shapes without using complicated molding tools. Compared to the conventional manufacturing methods, the developed one significantly decreases the consumption of nonrenewable resources, polymer waste generation, as well as manufacturing cost. It has the great potential to be applied to a wide variety of polymer systems.